Tổng hợp và nghiên cứu đặc trưng của vật liệu SBA-15, SBA-16 - Thuận, Ngô Thị; Trọng, Phạm Đình (Vietnam Journal of Chemistry, 2014)
SBA-15 and SBA-16 materials have controllable pore size and thick pore walls as well as much higher hydrothermal stability than M41S-type materials. They were prepared under acidic condition using Pluronic P123 (PEO20PPO70PEO20) and F127 (PEO106PPO70PEO106) as the structure-directing agents and tetraethylorthosilicate TEOS as the silica source, as described by Zhao et al [1] with the addition of inorganic salt. The samples were characterized by XRD, SEM, TEM, and BET techniques. It is revealed that SBA-16 has more excited properties than SBA-15 with cage-like pore and 3-D pore channel. But somehow it is more difficult to synthesize SBA-16 and investigate the structure of it than SBA-15.